Economic Peculiarities of the Romanian Tisa River Basin - ANA-MARIA POP; NICOLETA DAVID; SORIN FILIP; LELIA PAPP (Romanian Review of Regional Studies, 2010)
A possible answer to the current challenges of the Tisa catchment area, correlated with water management, social and economic development, environmental conservation, is the transnational initiative of the five countries drained by the tributaries of the Tisa River. In this context, the spatial development has a major impact on the Romanian Tisa catchment area by providing the economic cohesion. The purpose of the present paper is to define the current status of economy in the Romanian Tisa River Basin, through the filter of achieving the level of competitiveness claimed by the national, European, or global authorities. By setting several quantitative indicators, analyzed for a standard territorial level (NUTS 3), for a definite time interval (2002-2007), those more or less competitive economic branches, activities or aspects of the analyzed territory were identified, and, at the same time, the elements that “hinder” development, the traditional remnants, or the existing entrepreneurial initiatives. On the basis of relevant indicators, the calculation of an index of competitiveness was proposed at territorial level, the results certifying a certain level of competitiveness for the region under consideration.